La dimenticanza della polis nota su Heidegger e Platone - Amato, Pierandrea (Mechane, 2022)
The contribution examines excerpts from Heidegger’s 1942-43 university course on Parmenides, where he analyzes the original and metaphysical status of the Greek polis, in order to highlight how the age of technology coincides first and foremost with the era in which a political thought about politics tends to sunset.